Bad girl reputation eaudiobook - Kennedy, Elle (Avalon Bay, 2022)
Bestselling author Elle Kennedy returns to Avalon Bay in this sexy second chance story about two exes who can't stay away from each other, Bad Girl Reputation . When former bad girl Genevieve West returns home for her mother's funeral, she's prepared to keep her distance from her ex-boyfriend, Evan Hartley. Their history is rife with turbulence. And passion. A heck of a lot of passion...which she's trying desperately to forget. But it's impossible not to run into Evan in the small coastal town where they once ran wild. And the moment she sees her gorgeous ex again, it's clear to Gen that Evan is still as unruly, sexy, and irresistible as ever. This time around, however, she's resolved to walk a new path. No more partying. No more foolish mistakes. Her plan is to temporarily remain in town to help her father run his business, but the second he finds somebody else, she's out of there. Evan has other ideas. He knows they can be good together, but he just has to convince Genevieve of that, even if it means turning over a new leaf himself. But can a bad reputation ever truly be shed? Do second chances really work? Genevieve and Evan are about to find out. A Macmillan Audio production from St. Martin's Press.